ANALISIS KINERJA KEUANGAN PADA YAYASAN FRANKENMOLEN - Wahyu Agusti Sanggo; Daniel Nemba Dambe (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this research is to analyze the financial performance of Frankenmolen Foundation in terms of fiscal performance, non-program activity efficiency performance, and program efficiency performance. This research uses descriptive research methods with data collection techniques through documentation and interviews from the Frankenmolen Foundation. The data analysis instrument used is the financial ratio of non-profit organizations including fiscal performance, non-program activity efficiency performance ratio, and program efficiency performance ratio. The results showed that fiscal performance was classified as quite effective for total revenue divided by total costs, but ineffective for total revenue divided by total assets. In addition, the efficiency performance of non-program activities is classified as inefficient while the efficiency performance of the program is classified as efficient.